2002
DOI: 10.1159/000057595
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Is Unable to Reduce Dental Erosion from Soft Drinks

Abstract: The main aim of the present study was to compare the erosive capabilities of some fruit-flavoured drinks, fresh or saturated with CaF2, with their content of acids and with previous results from some carbonated soft drinks. The other aim was to measure and compare the rates of dissolution of CaF2 in some carbonated and non-carbonated drinks and water. Seven commercially available fruit-flavoured drinks were diluted for drinking. Two human molars, each with two approximately 4 × 4 mm windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
3
28

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 20 publications
9
84
3
28
Order By: Relevance
“…Fluoride did not provide a protective effect on enamel when present in acidic carbonated beverages (25). The tested black tea contains fluoride, but other ingredients are also present in its composition, such as citric acid and phosphoric acid, which might have contributed to its negative result in terms of decrease of enamel microhardness.…”
Section: Discussionmentioning
confidence: 81%
“…Fluoride did not provide a protective effect on enamel when present in acidic carbonated beverages (25). The tested black tea contains fluoride, but other ingredients are also present in its composition, such as citric acid and phosphoric acid, which might have contributed to its negative result in terms of decrease of enamel microhardness.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of fluoride on dental erosion has been studied under various conditions with conflicting results. 19,26,27 It is possible that increasing the fluoride concentration in acidic drinks could contribute to reduce their erosive potential. However, a review paper showed that fluoride admixtures to acidic solutions in a concentration excluding toxicological side effects seem unable to arrest erosive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to protect the tooth surface completely, it has been suggested that the CaF 2 -like layer should be dense enough to build up a physical barrier, which protects the underlying enamel form acid attack, and it should be sufficiently stable against erosive dissolution (6). Although several studies have shown that application of high-concentrated fluoride can increase acid resistance of human enamel (7,29,30), a study demonstrated that fluoride does not provide protective effects against erosion from carbonated soft drinks (13).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, toothpaste fluoridation has been shown to decrease the development of erosion in situ (11,12). In contrast, several studies have demonstrated that fluorides cannot prevent dental erosion (13,14).…”
Section: Introductionmentioning
confidence: 99%